Characterisation of phosphorylated nucleotides by collisional and electron‐based tandem mass spectrometry. (5th September 2016) - Ball, Andrew T.; Prakash, Aruna S.; Bristow, Anthony W.T.; Sims, Martin; Mosely, Jackie A.
Abstract : Rationale: Tandem mass spectrometry of phosphorylated ions can often yield a limited number of product ions owing to the labile nature of phosphate groups. Developing techniques to improve dissociation for this type of ion has implications for the structural characterisation of many different phosphorylated ions, such as those from nucleotides, pharmaceutical compounds, peptides and polymers. Methods: Solutions of adenosine monophosphate, diphosphate and triphosphate (AMP, ADP and ATP) were studied in a hybrid linear ion trap–Fourier transform ion cyclotron resonance (FTICR) mass spectrometer. Precursor ions with an overall single positive charge, including protonated nucleotides or nucleotide cations containing one, two or three sodium atoms, were isolated for tandem mass spectrometry. Collision‐induced dissociation (CID) was performed in the linear ion trap, with electron‐induced dissociation (EID) being conducted in the FTICR cell. Results: EID resulted in many product ions not seen in CID. EID product ion spectra were seen to vary for AMP, ADP and ATP when the nucleotide cation contained zero, one, two or three sodiums. Precursor cations that contain two or three sodiums mainly formed product ions derived from the phosphate group. Conversely, when a precursor ion containing no sodium underwent EID, product ions mainly relating to the non‐phosphate end of the ion were observed. The number of phosphate groups was not seen to greatly affect either CID or EID product ion spectra. Conclusions: The presence of sodium in a precursor ion directs electron‐induced bond dissociation, thus enabling targeted, and therefore tuneable, fragmentation of groups within that precursor ion. For all precursor ions, the most useful product ion spectra were obtained by EID for a precursor ion containing one sodium, with bond dissociation occurring across the entire nucleotide cation. The findings of this study can be used to improve the structural elucidation of many phosphorylated molecules by broadening the range of product ions achievable. © 2016 The Authors. Rapid Communications in Mass Spectrometry Published by John Wiley & Sons Ltd.